2009
DOI: 10.1124/dmd.109.028340
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Role of Metabolites in (±)-3,4-Methylenedioxymethamphetamine-Induced Serotonergic Neurotoxicity

Abstract: ABSTRACT:The mechanism by which the recreational drug (؎) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 36 publications
6
55
0
1
Order By: Relevance
“…Previous studies showed that HHMA and HMMA are formed in vivo after MDMA administration in both rats and humans (Lim et al, 1992;Segura et al, 2001;Valtier et al, 2007;Goni-Allo et al, 2008;Kolbrich et al, 2008b;Mueller et al, 2009), but there is uncertainty about whether these hydroxylated metabolites represent major MDMA metabolites in rodents. Here we observed that AUCs for HHMA and HMMA were always greater than AUC for MDMA in rats given 2.5 mg/kg, confirming that O-demethylenation is the predominant pathway for biotransformation in rats given clinically relevant MDMA doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that HHMA and HMMA are formed in vivo after MDMA administration in both rats and humans (Lim et al, 1992;Segura et al, 2001;Valtier et al, 2007;Goni-Allo et al, 2008;Kolbrich et al, 2008b;Mueller et al, 2009), but there is uncertainty about whether these hydroxylated metabolites represent major MDMA metabolites in rodents. Here we observed that AUCs for HHMA and HMMA were always greater than AUC for MDMA in rats given 2.5 mg/kg, confirming that O-demethylenation is the predominant pathway for biotransformation in rats given clinically relevant MDMA doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have examined MDMA pharmacokinetics in rats given doses of ,10 mg/kg, comparable to those taken by humans (Chu et al, 1996;Starr et al, 2008;, and just one assessed the relationship between pharmacodynamics and pharmacokinetics (Chu et al, 1996). Most MDMA pharmacokinetic studies in rats investigated doses of 10 mg/kg or higher (Valtier et al, 2007;Meyer et al, 2008;Upreti and Eddington, 2008;Mueller et al, 2009). In two rat studies employing doses of ,10 mg/kg, evidence for MDMA nonlinear accumulation was reported (Chu et al, 1996;), similar to the human situation (Mas et al, 1999;de la Torre et al, 2000;Kolbrich et al, 2008b).…”
mentioning
confidence: 99%
“…Neurotoxic effects to serotonic neurons have been described, but are still controversial discussed in terms of species and dosing [7][8][9]. MDMA metabolism is suspected to be responsible for neurotoxicity presumably through the formation of glutathion adducts [10][11][12][13][14][15][16]. HMMA can be further conjugated by UDP-glucuronyltransferases or by sulfotransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism of MDMA may play a role in this neurotoxicity (Miller et al, 1997;Bai et al, 1999;Mueller et al, 2009). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%